Emerging Nanotechnology for Treatment of Alzheimer’s and Parkinson’s Disease - Li, Amanda; Tyson, Joel; Patel, Shivni; Patel, Meer; Katakam, Sruthi; Mao, Xiaobo; He, Weiwei (Frontiers in Bioengineering and Biotechnology, 2021)
The prevalence of the two most common neurodegenerative diseases, Parkinson’s disease (PD) and Alzheimer’s Disease (AD), are expected to rise alongside the progressive aging of society. Both PD and AD are classified as proteinopathies with misfolded proteins α-synuclein, amyloid-β, and tau. Emerging evidence suggests that these misfolded aggregates are prion-like proteins that induce pathological cell-to-cell spreading, which is a major driver in pathogenesis. Additional factors can further affect pathology spreading that includes oxidative stress, mitochondrial damage, inflammation, and cell death. Nanomaterials present advantages over traditional chemical or biological therapeutic approaches at targeting these specific mechanisms. They can have intrinsic properties that lead to a decrease in oxidative stress or an ability to bind and disaggregate fibrils. Additionally, nanomaterials enhance transportation across the blood-brain barrier, are easily functionalized, increase drug half-lives, protect cargo from immune detection, and provide a physical structure that can support cell growth. This review highlights emergent nanomaterials with these advantages that target oxidative stress, the fibrillization process, inflammation, and aid in regenerative medicine for both PD and AD.